Studi Pengobatan Diabetes Melitus Tipe 2 dengan Komplikasi Hipertensi di Instalasi Rawat Jalan RSU dr. H. Koesnadi Bondowoso Periode Tahun 2014 (Study of Treatment of Type 2 Diabetes Mellitus with Hypertension in Outpatient Departement of dr. H. Koesnadi - Sendika Widi Saputri; Antonius Nugraha Widhi Pratama; Diana Holidah (Pustaka Kesehatan, 2016)
Diabetes mellitus (DM) is a chronic disorder characterized by hyperglycemia caused by disruption of glucose metabolism in the body. Non-insulin dependent DM or type 2 DM can progress into macrovascular complication such as hypertension. The aim of this study was to examine treatment profile of patients with type 2 DM and hypertension. This consecutive cross sectional research used the data taken from medical records of ambulatory patients visiting dr. H. Koesnadi Bondowoso during January to December 2014. A number of 205 patients were included in the study consisting of 125 (60.1%) females and 80 (39.0%) males. Most patients (180 patients, 78.2%) were aged 50-69 years. One hundred and eighty-seven patients received antidiabetic and antihypertensive therapy, 4 patients were without antidiabetic therapy and 14 patients without antihypertensive therapy. Inappropiate combination of medications occured among 71 patients. Moreover,12 patients were found under dosed. Keywords: diabetes mellitus, hypertension, antidiabetic, antihypertensive, outpatient